2016
DOI: 10.1016/j.theriogenology.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Storage of sexed boar spermatozoa: Limits and perspectives

Abstract: Despite the great potential application of sex-sorted spermatozoa in swine, the technology is not practiced in the pig industry because of technical factors and species-specific issues. The susceptibility of boar spermatozoa to stresses induced by the sorting procedure, the relative slowness of the sex-sorting process together with the high sperm numbers required for routine artificial insemination in pig are some of the main factors limiting the commercial application of this technology in pigs. This review b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 80 publications
0
6
0
1
Order By: Relevance
“…Some of these obstacles could be overcome by adopting a sperm encapsulation technique, which was previously demonstrated in bovine [13171836] and swine [78232930313334] species with promising results. Alginate encapsulation of sperm can limit damage to spermatozoa and allow prolonged sperm release; moreover, the bioadhesiveness of alginate can prevent semen backflow.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these obstacles could be overcome by adopting a sperm encapsulation technique, which was previously demonstrated in bovine [13171836] and swine [78232930313334] species with promising results. Alginate encapsulation of sperm can limit damage to spermatozoa and allow prolonged sperm release; moreover, the bioadhesiveness of alginate can prevent semen backflow.…”
Section: Introductionmentioning
confidence: 99%
“…Rataan viabilitas selama penyimpanan (%) ± SD Verbeckmoes et al (2004;2005) bahwa pengencer harus mempunya komposisi yang sama dengan komposisi ion, pH maupun osmolaritas seperti pada epididimis sehingga spermatozoa dapat disimpan seperti penyimpanan yang terjadi dalam epididimis. Spinaci et al (2015) menjelaskan bahwa viabilitas spermatozoa menurun karena fosfolipid pada membran sel spermatozoa mengalami kerusakan permanen sehingga terjadi penurunan fungsi membran sel.…”
Section: Persentase Viabilitas Spermatozoa Selama Penyimpanan Suhu 3-...unclassified
“…Therefore, under this scenario, cryopreservation seems the only useful method to store boar sex-sorted sperm AI-doses. We have demonstrated that sex-sorted and cryopreserved boar spermatozoa show acceptable recovery rates in terms of motility and viability after thawing [46], but unfortunately they achieve poor fertility after AI [47]. Consequently, further research, aimed at optimizing cryopreservation protocols is required before sex-sorted sperm can be commercially used.…”
Section: Daily Use Of Frozen-thawed Semen and Of Sex-sorted Sperm In mentioning
confidence: 99%
“…New extenders for extending lifespan of FT-sperm and for cryopreserving sexed sperm are imperative [30,47].…”
Section: Seminal Plasma a Mine To Fully Discovermentioning
confidence: 99%